Talempong Unggan Sumpur Kudus Kabupaten Sijunjung Dalam Film Dokumenter - ZULMAIDI, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Talempong Unggan is an art that exist in Nagari Unggan Sumpur Kudus Sijunjung regency of West Sumatra. The community does not recognize the cultures contained in the traditional art of Talempong Unggan and the lack of government attention in preserving the traditional art of Talempong Unggan become the main factor of the writer to make a documentary film related to culture in Talempong Unggan traditional art. The approach methodology departs from several literatures and uses the 5W + 1H method by understanding all information and a problem. So the selection of promotional media is more effective and the message conveyed is understood by the target audience. So all aspects are summarized in traditional art Talempong Unggan packed in documentary film media, so that Documentary Film Talempong Unggan Sumpur Kudus Sijunjung District became an effective and communicative media. Documentary film is one of the effective media because the delivery of information through documentary film more easily attract the attention of the target audience. The purpose of this documentary is to provide information on the history and culture of accompaniment with the traditional art of talempong Unggan. In addition to documentary films are supported by several other media that help mainstream media to introduce subjects to target audience ie posters, stickers, shirt, paper bag, dvd cover, dvd label, pin and backdrop.Keywords: Documentary film, Talempong Unggan.